Tanshinone IIA alleviates atherosclerosis in LDLR−/− mice by regulating efferocytosis of macrophages - Wang, Jiarou; Zhang, Yifan; Feng, Xiaoteng; Du, Min; Li, Sijin; Chang, Xindi; Liu, Ping (Frontiers in Pharmacology, 2023)
Background: Tanshinone IIA (TIIA) is the major lipid-soluble active ingredient of the traditional Chinese medicine Salvia miltiorrhiza, which slows down atherosclerosis (AS). However, it remains unclear whether TIIA has the potential to enhance macrophage efferocytosis and thereby improve AS. Objective: The focus of this examination was to determine if TIIA could reduce lipid accumulation and treat AS by enhancing efferocytosis. Methods: Firstly, we conducted in vivo experiments using LDLR knockout (LDLR-/-) mice for a period of 24 weeks, using histopathological staining, immunofluorescence and Western Blot experiments to validate from the efficacy and mechanism parts, respectively; in addition, we utilized cells to validate our study again in vitro. The specific experimental design scheme is as follows: In vivo, Western diet-fed LDLR-/- mice for 12 weeks were constructed as an AS model, and normal diet-fed LDLR-/- mice were taken as a blank control group. The TIIA group and positive control group (atorvastatin, ATO) were intervened for 12 weeks by intraperitoneal injection (15 mg/kg/d) and gavage (1.3 mg/kg/d), respectively. In vitro, RAW264.7 cells were cultured with ox-LDL (50 ug/ml) or ox-LDL (50 ug/ml) + TIIA (20 uM/L or 40 uM/L). Pathological changes in aortic plaques and foam cell formation in RAW264.7 cells were evaluated using Masson and Oil Red O staining, respectively. Biochemical methods were used to detect lipid levels in mice. The immunofluorescence assay was performed to detect apoptotic cells and efferocytosis-related signal expression at the plaques. RT-qPCR and Western Blot were carried out to observe the trend change of efferocytosis-related molecules in both mouse aorta and RAW264.7 cells. We also used the neutral red assay to assess RAW264.7 cells' phagocytic capacity. Results: Compared with the model group, TIIA decreased serum TC, TG, and LDL-C levels (P<0.01), reduced the relative lumen area of murine aortic lipid-rich plaques (P<0.01), enhanced the stability of murine aortic plaques (P<0.01), reduced ox-LDL-induced lipid build-up in RAW264.7 cells (P<0.01), and upregulated efferocytosis-related molecules expression and enhance the efferocytosis rate of ox-LDL-induced RAW264.7 cells. Conclusion: TIIA might reduce lipid accumulation by enhancing the efferocytosis of macrophages and thus treat AS.